Impedance cardiography – optimization and efficacy evaluation of antihypertensive treatment - Panasiuk-Kamińska, Katarzyna; Szeliga-Król, Jolanta; Zubilewicz, Renata; Jaroszyński, Andrzej (Family Medicine & Primary Care Review, 2016)
Background . Hypertension is a civilization disease which currently affects about 10.5 m people in Poland. The number of patients with diagnosed, untreated hypertension amounts to 18%, and as many as 45% of patients are treated ineffectively whereas only 26% are treated effectively. Impedance cardiography (IC) is an important tool both in diagnostics and the treatment of hypertensive patients, particularly in the case of antihypertensive treatment resistance. This method allows for the individualized treatment of each patient on the basis of hemodynamic parameters, monitoring of hypertensive patients in the outpatient care setting, and the assessment of cardiovascular risk factors. Objectives . The aim of the study was to evaluate the efficacy of hypotensive medications in patients with hypertension using impedance cardiography. Material and methods. The study involved 60 hypertensive patients, treated with antihypertensives, who failed to achieve the required blood pressure values. The modification of hypertension therapy was based on EBM (evidence-based medicine) and on hemodynamic parameters obtained using impedance cardiography. Results . It was found that high blood pressure therapy based on impedance cardiography parameters has a significant influence on blood pressure reduction compared to EM B-based therapy: below 140/90: 66.8 vs. 55.1% and below 130/80: 23.5 vs. 18.9%. Conclusions . On the basis of this study it was confirmed that impedance cardiography allows for a significant reduction of hypertension and the selection of the most effective therapeutic strategy, providing for the optimization and efficacy of hypertension treatment.